Whole effluent toxicity (WET) testing of tin mining effluent and receiving water on zebrafish, Danio rerio (Hamilton, 1822) - Ahmad Affandi, Farhana; Ishak, Mohd Yusoff; Samsudin, Nur Hamizah (Universiti Putra Malaysia Press, 2019)
Mining is one of the anthropogenic activities that can negatively affect the environment especially the waterways. Discharges from mining activities are usually in acidic state and containing elevated concentrations of metals. The exposure to these contaminants may cause several harmful effects not only to aquatic organisms but also to human health. The Whole Effluent Toxicity (WET) test was applied to evaluate the toxic effects of tin mining effluents to aquatic organisms. An acute toxicity test with zebrafish (Danio rerio) was conducted where fish was exposed to 3.13%, 6.25%, 12.5%, 25% and 50% effluent for 96 hours under static renewal test system. Effects of effluent exposure were determined using endpoints with mortality of median lethal concentration (LC50) value. Results indicated that the LC50 value of zebrafish when exposed, was 14.21% effluent. The physicochemical properties of the effluent were also evaluated in order to assess the cause-effect relationships of the effluent. The low pH values of the mine effluent might be the main reason contributing to the fish mortality. This approach provides additional information of tin mining effect on freshwater fishes as well as to human health.